2019
DOI: 10.1002/dmrr.3223
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis on the efficacy and safety of SGLT2 inhibitors and incretin based agents combination therapy vs. SGLT2i alone or add‐on to metformin in type 2 diabetes

Abstract: We aimed to determine whether sodium-glucose cotransporter type 2 inhibitors (SGLT2is) and incretin-based agents combination therapy produces more benefits than SGLT2is alone in patients with type 2 diabetes mellitus (T2DM). PubMed, Embase, and the Cochrane Library were searched for randomized controlled trials (RCTs) comparing SGLT2is plus Dipeptidyl-Peptidase 4 inhibitors (SGLT2is/DPP4is) or glucagon like peptide-1 receptor agonists (SGLT2is/GLP-1RAs) against SGLT2is as monotherapy or add-on to metformin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Canagliflozin and other SGLT2 inhibitors have been shown to reduce hospitalizations for HF and renal events 2‐5 in patients with T2DM and recently also in patients without T2DM 5,28 . Canagliflozin was shown to reduce cardiovascular and renal events, including hospitalizations for HF, even in patients with chronic kidney disease and albuminuria, 29 further supporting its role in patients with T2DM to reduce cardiovascular events.…”
Section: Discussionmentioning
confidence: 93%
“…Canagliflozin and other SGLT2 inhibitors have been shown to reduce hospitalizations for HF and renal events 2‐5 in patients with T2DM and recently also in patients without T2DM 5,28 . Canagliflozin was shown to reduce cardiovascular and renal events, including hospitalizations for HF, even in patients with chronic kidney disease and albuminuria, 29 further supporting its role in patients with T2DM to reduce cardiovascular events.…”
Section: Discussionmentioning
confidence: 93%
“…This finding has important implications in the routine care of T2D because DPP‐4i have become popular second‐line GLM worldwide and in Italy, 35 despite they are devoid of solid cardio‐renal protective effects 36 . We recognize that combination therapy with SGLT2i and DPP‐4i or incretin‐based therapies in general, which has recently become available in many countries, can provide an additional benefit on several clinical outcomes 37 …”
Section: Discussionmentioning
confidence: 99%
“…39 Notably, based on data from the DURATION-8 trial, which reported both short-term and long-term results, the overall body SGLT2i has been addressed in four previous meta-analyses. [7][8][9][10] However, these meta-analyses only synthesized data from comparisons with an SGLT2i. Instead, we also analysed studies and study arms that included a GLP-1RA as a comparator.…”
Section: Mortality and Cardiovascular Outcomesmentioning
confidence: 99%
“…[7][8][9][10] However, either they focused solely on comparisons with SGLT2is and not with GLP-1RAs and did not incorporate data from all relevant randomized controlled trials (RCTs) published to date, or they did not take into consideration the pattern of combination therapy in each trial (sequential administration or co-initiation) in their analysis. [7][8][9][10] Sequential administration aims to improve patient adherence and minimize adverse events, while co-initiation therapy can lead to earlier achievement of therapeutic goals by targeting multiple pathogenic mechanisms simultaneously, as shown in the VERIFY (Vildagliptin Efficacy in combination with metfoRmIn For earlY treatment of type 2 diabetes) study. 11,12 We aimed to systematically retrieve, critically appraise and synthesize all currently available evidence evaluating the efficacy and safety of combination therapy with a GLP-1RA and an SGLT2i in patients with type 2 diabetes, by means of an up-to-date systematic review and meta-analysis of RCTs.…”
Section: Introductionmentioning
confidence: 99%